Does "smoker's paradox" exist in clopidogrel-treated Turkish patients with acute coronary syndrome. (2nd April 2016) - Edem, Efe; Kirdök, Ali Hikmet; Kınay, Ahmet Ozan; Tekin, Ümit İlker and Taş, Sedat and Alpaslan, Erkan and Pabuccu, Mustafa Türker and Akdeniz, Bahri
Abstract: Previously conducted studies revealed that smoking enhanced the efficacy of clopidogrel by increasing formation of the active metabolite (AM) from the prodrug through induction of the cytochrome CYP1A2. The expression of cytochrome enzymes depends on genotype and no data exists in literature conducted in Turkish patients comparing the clopidogrel responsiveness between active smokers and non-active smokers treated with clopidogrel. In this study, our aim was to investigate the clopidogrel responsiveness in clopidogrel-treated Turkish acute coronary syndrome (ACS) patients according to their smoking status. We retrospectively enrolled 258 patients who were hospitalized due to ACS. Clinical variables of the patients, especially smoking status were recorded. Clopidogrel resistance was evaluated by using adenosine diphosphate (ADP) induced platelet aggregometry. Clopidogrel resistance was detected as a change in maximal aggregation ≤20% from baseline. A total of 139 patients were active smokers while 12 were former smokers. 107 patients did not have a history of smoking. Ten of the smokers were hyporesponsive to clopidogrel, whereas 36 of non-smokers were hyporesponsive to clopidogrel ( p < 0.001). Receiver-operating characteristic curve analysis demonstrated that Au-min value >612.5 predicted the clopidogrel resistance with a sensitivity of 60% (OR: 100.65, %95 CI = 19.996–506.615 p < 0.001). Results of this study demonstrated that ADP responses were lower in smokers receiving clopidogrel and aspirin than in non-smokers receiving the same drug regimen. This finding indicates that smoking was related to an enhanced clopidogrel responsiveness in Turkish patients hospitalized due to ACS, suggesting that "smoker's paradox" probably exists in Turkish ACS patients.